Investigation of supercapacitor properties of chlorine-containing functional groups doped graphene electrodes - Arvas, Melih Besir; Gencten, Metin; Sahin, Yucel (ELSEVIER SCIENCE SA, 2022)
In this study, the supercapacitor performances of chlorine-containing functional groups-doped graphene-based electrodes, environmentally friendly synthesized in one step by Yucel's method, were investigated for the first time in the literature. The formation of graphene layers in the mesoporous structure was determined by scanning electron microscopy. Functional molecular groups such as-Cl,-ClO3,-ClO4, and hydroxyl formed on the electrode surface were characterized by X-ray photoelectron spectroscopy. Cyclic voltammetry and electrochemical impedance spectroscopy were used for the electrochemical characterization of the electrodes. In electrochemical impedance spectra, capacitance values and Warburg impedance values wereincreased by doping chlorine-containing functional groups to the graphene electrode surface. Besides, cyclic charge-discharge tests were also performed for 1000 cycles to determine the cyclic stability of the electrode materials. The electrodes lost an average of 5% of their capacitances at the end of the 1000 cycles. As the number of cycles increased during the synthesis of the electrodes, the quantity of different molecular functional groups on the surface increased. In this respect, the electrode surface became more accessible for electrolyte penetration as a function of the increasing cycle. Eventually, the areal capacitance of the electrodes demonstrated an increasingly changing from 248.5 mF.cm(-2) to 2531 mF.cm(-2) at a current density of 10 mA.cm(-2 )with respect to their chemical and physical structure.
Keywords: EDLC; Graphene electrodes; Chlorine-doped graphene; Supercapacitor; Cyclic voltammetry; CARBON; OXIDE; NITROGEN; PERFORMANCE; NANOSHEETS; EFFICIENT; REDUCTION; GRAPHITE; FILM; Chemistry; Electrochemistry